Accessory belly of flexor digitorum superficialis - case report of a rare variant - Choudhary, Umesh; Patil, Shrish S.; G.M., Mahesh; Singh, Amit K. (International Journal of Research in Medical Sciences, 2017)
Variations of the muscles pose a challenge to diagnosis and knowledge about them is important during surgeries and other interventions. At times these variations may cause symptoms per se. Variations of the Flexor digitorum superficialis: a muscle of the anterior compartment of forearm, are not very common. We present a rare variation of this muscle in the right upper limb of a male cadaver. The variant was an accessory belly arising from and under the Flexor digitorum superficialis and inserting into the base of proximal phalanx of the index finger. We also review the evolutionary and embryological concepts of such variations.